1997
DOI: 10.1182/blood.v89.10.3745
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Anthracycline Accumulation in Doxorubicin-Selected U-937 Cells: Participation of Lysosomes

Abstract: The U-A10 cell line, a doxorubicin-selected variant of human U-937 myeloid leukemia cells, exhibits a redistribution of anthracyclines into a expanded vesicular compartment. The acidic nature of this compartment was confirmed by vital staining with a pH sensitive dye, LysoSensor yellow/blue DND-160. Identification of the vesicular compartment was performed by immunofluorescence analysis. Staining for the LAMP-1 and LAMP-2 antigens showed that the vesicles are enlarged lysosomes that are eccentrically placed ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…9,10 In addition, some cancer cells have been shown to acquire an enhanced capacity to sequester anticancer drugs in their lysosomes, and this is considered to be a mechanism for multidrug resistance. [11][12][13] Drug accumulation in lysosomes also has potential toxicological ramifications. The extensive lysosomal accumulation of a number of cationic amphiphilic drugs has been associated with the development of drug-induced phospholipidosis; the long-term consequences of this, if any, are controversial and not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In addition, some cancer cells have been shown to acquire an enhanced capacity to sequester anticancer drugs in their lysosomes, and this is considered to be a mechanism for multidrug resistance. [11][12][13] Drug accumulation in lysosomes also has potential toxicological ramifications. The extensive lysosomal accumulation of a number of cationic amphiphilic drugs has been associated with the development of drug-induced phospholipidosis; the long-term consequences of this, if any, are controversial and not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular pH in tumor-derived cells was measured in several studies. The vesicles in which drugs accumulated have been identified as lysosomes, (3,4) endosomes, (5) and vesicles of the Golgi compartment, (6,7) all of which are acidic organelles. Many anticancer agents, such as doxorubicin (ADM), daunorubin, vincristine (VCR), and mitoxantrone, are weak bases with pK a values between 7.4 and 8.4.…”
mentioning
confidence: 99%
“…(10) Agents that disrupt organelle acidification should increase drug sensitivity. Treatments of resistant cells with reagents that are known to increase the pH of endomembrane compartments block the vesicular accumulation of chemotherapeutic drugs (4,5) and increase the cytotoxicity of anticancer agents.…”
mentioning
confidence: 99%
“…Logically, any weakly basic compound will tend to accumulate in any membrane-bound compartment that has a lower internal pH than external pH. Previous studies have indicated that drugs accumulate in Golgiderived vesicles [13,31,32], endosomes [13] and lysosomes [13,33,34]: all of which are more acidic than the cytosol. The cytosol of most cells has a pH of 7.2-7.3, by contrast, the lumena of recycling endosomes and trans-Golgi network have a pH of 6.0-6.3, and the pH of lysosomes can be lower than 4.5.…”
Section: Discussionmentioning
confidence: 99%